Two New Hot-Vent Peltospirid Snails (Gastropoda: Neomphalina) from Longqi Hydrothermal Field, Southwest Indian Ridge - Chen, Chong; Zhou, Yadong; Wang, Chunsheng; Copley, Jonathan T. (Frontiers in Marine Science, 2017)
The Longqi hydrothermal vent field is the first deep-sea active vent field to be explored on the ultra-slow spreading Southwest Indian Ridge. Although a number of larger taxa has been described or characterised, many smaller and less conspicuous animals remain undescribed. Here, two small (< 7 mm) coiled gastropods belonging to the vent-endemic family Peltospiridae are characterised and formally named from Longqi. Lirapex politus n. sp. is characterised by its entirely smooth shell lacking in axial sculpture, which distinguishes it from the three described congeners from East Pacific Rise and Mid-Atlantic Ridge. Dracogyra subfuscus n. gen., n. sp. is conchologically most similar to Depressigyra globulus from the northeastern Pacific, differing in having an almost closed umbilicus and lacking a basal notch in the outer lip. Radula characteristics clearly distinguish the two, however, with Dracogyra n. gen. having a much wider, shorter, sturdier central tooth and stronger laterals. Molecular phylogeny reconstruction using the cytochrome c oxidase I (COI) barcoding fragment indicate that Dracogyra n. gen. is in fact most closely related to Gigantopelta and Lirapex is sister to Pachydermia. The pairwise distance in COI between Dracogyra n. gen. and other peltospirid genera (14.4%~26.6%, mean 21.3%) are sufficient to justify separate genera. Both new species were found around diffuse flow venting areas in association with giant holobiont peltospirid snails Chrysomallon and Gigantopelta. The addition of these two new species increases the total macrofauna species known from Longqi field to 23.